Model Uncertainty Effect on Asset Prices*. (1st March 2017) - Jiang, Junya; Tian, Weidong
Abstract: We develop a weighted‐average approach of pricing under model uncertainty, where several plausible models are considered instead of a perfect one. The model uncertainty effect from this weighted‐average approach is significantly different from the conventional wisdom, in which the true price must be bounded by prices in all plausible models. We identify under what circumstances the model uncertainty effect is significant and reveal serious risk management challenges for researchers, regulators, and market participants.